Antimicrobial and Cytotoxic activity of rhizome extract of Acorus calamus (Bojho) in combination with different antimicrobial agents: Synergistic Effects - Khanal, Hemanta (International Journal of Applied Sciences and Biotechnology, 2019)
Acorus calamus (sweet flag) is a monocot plant found in wetland, have the scented leaves and rhizomes. Various active bio-ingredients of A. calamus had been studied and characterized and some of them are known for antimicrobial and antitumor activities. The dry rhizomes were powdered ethanolic extraction was performed in a Soxhlet apparatus. The extract was dried and re-suspended to sterile distilled water and sterilized by membrane filtration. The synergist affects against bacteria, fungi, helminths were evaluated and cytotoxic assay was performed. The minimum inhibitory concentrations of plant extract was found to be 50µg/ml for the vancomycin resistance Staphylococcus aureus, for extended spectrum beta lactamase Escherichia coli, Methicillin resistant S. aureus, were 100 µg/ml. Synergistically cefixime and cefpodoxime both antibiotics are found to be effective against all strains of S. aureus and E. coli except VRSA. The antifungal characteristics were found to be effective when agar cup diffusion were performed in combination with fluconazole antifungal drug. The combination of plant extract was more effective anthelminthic drug than the anthelminthic drug alone. Similarly, the plant extract has lethal concentration 50 (LC50) was found to be 173.3 µg / ml and LC90 was 555. 4 µg / ml on brine shrimp. The A. calamus has potential characteristics to be as antimicrobial and antitumor medicine when used synergistically with antimicrobial agents.